KONSELING DAN PLURALISME AGAMA DALAM MEDITASI DI VIHARA KARANGDJATI YOGYAKARTA - Bigmen Pangestu (INSTITUT AGAMA ISLAM NEGERI METRO, 2020)
Using Meditation as a medium in Counseling makes the counseling process fresher and more interesting. Because one of the challenges a counselor must face in the interfaith Guidance and Counseling process is how to respond to religious differences. Religious differences should not be an obstacle in the counseling process. Understanding religious pluralism is a need for a counselor in the counseling process in a pluralistic society. Religious pluralism is based on the assumption that all existing religions are equally valid paths to God. The practice of meditation at Vihara Karangdjati is a clear example of the attitude of pluralism. There, people from different religious backgrounds gather and socialize in a peaceful and understanding manner between religions. Counseling and religious pluralism in meditation at Vihara Karangdjati is the provision of counseling services to meditation participants of different beliefs or religions with a meditation guide as a counselor. The awareness of the guides and meditation participants on religious pluralism makes the process of meditation as interfaith counseling run well